2013
DOI: 10.1038/ejcn.2013.52
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a dairy- and calcium-rich diet on weight loss and appetite during energy restriction in overweight and obese adults: a randomized trial

Abstract: Background/ObjectivesA diet rich in dairy and calcium (Ca) has been variably associated with improvements in body composition and decreased risk of type 2 diabetes. Our objective was to determine if a dietary pattern high in dairy and Ca improves weight loss and subjective appetite to a greater extent than a low dairy/Ca diet during energy restriction in overweight and obese adults with metabolic syndrome.Subjects/Methods49 participants were randomized to one of two treatment groups: CONTROL [low dairy, ~700 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 40 publications
2
70
1
3
Order By: Relevance
“…Another study indicated that Mg supplementation improves lipid metabolism and reduces vulnerability to oxygen-derived free radicals (Dickens et al, 1992;Shechter, 2010). Ca supplementation improves serum cholesterol levels, hypertension, diabetes, and weight regulation (Villegas et al 2009;Jones et al 2013). It has been reported that Ca supplementation might ultimately reduce the occurrence of cardiovascular disease and has been recommended for elderly people and postmenopausal women to maintain bone health (Li et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Another study indicated that Mg supplementation improves lipid metabolism and reduces vulnerability to oxygen-derived free radicals (Dickens et al, 1992;Shechter, 2010). Ca supplementation improves serum cholesterol levels, hypertension, diabetes, and weight regulation (Villegas et al 2009;Jones et al 2013). It has been reported that Ca supplementation might ultimately reduce the occurrence of cardiovascular disease and has been recommended for elderly people and postmenopausal women to maintain bone health (Li et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The only product from that group whose higher intake resulted in a lower risk of obesity and positive changes in body mass or waist circumference was yoghurt. Jones et al carried out research on people who they divided into two groups [28]. The first group consumed products that contained a high amount of dairy and calcium; the second group consumed foods with a low amount of those elements.…”
Section: Discussionmentioning
confidence: 99%
“…Although some show highcalcium intake reduces appetite, these responses have, to date, been exclusively studied under energy-restriction. [11][12][13][14] The present study provides evidence that calcium supplementation may not influence appetite sensations (in the fasted state) under ad libitum feeding, and therefore, might not result in spontaneous energy restriction. This should however be confirmed by measures of energy intake under free-living conditions and with postprandial measures of appetite and metabolism, as nutritional status can influence appetite and metabolic responses to exercise.…”
mentioning
confidence: 95%
“…4 The reduction in appetite observed with acute calcium intake [6][7][8] may translate into a chronic reduction in appetite. [11][12][13][14] The mechanism(s) underlying a change in fat utilization with calcium intake, in humans, is not clear. Most evidence comes from in vitro or animal data, and the most prominent theory is currently that of parathyroid hormone (PTH) and/or 1,25(OH) 2 D regulating lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%